Sistem Penunjang Keputusan Penilaian Kinerja Menggunakan Metode Fuzzy Mamdani untuk Menentukan Status Karyawan - Lena Magdalena; Ridho Taufiq Subagio; Ida Wati (Prosiding SISFOTEK, 2024)
Employee performance appraisal is a performance management process in the company that functions as one of the decision-making for employee performance appraisal. At the Cirebon Non-Container Terminal PTP, a performance assessment has been carried out, but there are weaknesses, one of which is an input error in conducting an assessment which can directly change several components of the performance assessment so that the performance assessment decision is not accurate. The creation of a performance appraisal decision support system to determine the status of employees using the fuzzy mamdani method, produces a decision on employee performance appraisal recommendations and serves as a basis for consideration to change the status of employees who are still on contract to permanent employees. In this study, the tool used is Matlab (Matrix Laboratory) to compare the results graphically and the decision support system to be designed. The fuzzy mamdani method is applied with three assessment criteria, namely good, sufficient, and poor, this helps in making monthly decisions regarding the results of performance appraisals which are then recapitulated at the end of the year. The results of the calculation between Matlab and the Decision Support System using the fuzzy mamdani method show that the final score has a difference that is not much different, meaning that the fuzzy mamdani method has proven to be effective for employee performance assessment by producing accurate assessment decisions.